Evaluación de la capacidad de remoción de plomo y cadmio en soluciones acuosas utilizando resinas de carbón mineral (2019)
In the present investigation, an alternative treatment for the removal of lead and cadmium from aqueous solutions by means of an adsorbent material made from modified mineral coal impregnated with carbon disulphide and sodium hydroxide was considered. The material used was chemically characterized, the effect of pH on removal, adsorption kinetics (using Lagergren and Ho and McKay models) and Langmuir and Freundlich isotherms were evaluated in order to evaluate the adsorption capacity of modified coal. The results of the characterization of the coal showed that it is of metallurgical type, for its high content of volatile material and low content of Sulphur, as well as of ashes that makes it effective for the combustion and generation of energy. Tests to evaluate the effect of pH on adsorption determined that the best removal of lead and cadmium was at pH 6, for both materials, with adsorption percentages of 99.75 % and 99.85% for lead and cadmium with modified carbon and 75% and 52.5 for lead and cadmium with unmodified carbon. Kinetic studies indicated that the adsorption process reaches equilibrium in 100 minutes with 19.95 mg/g for lead and 19.94 mg/g for cadmium, following the kinetic model of pseudo second order for both metals. The isothermal study showed that the adsorption of Lead and Cadmium in the modified carbon is better suited to a Freundlich isotherm. In addition, a laboratory scale application test was performed with industrial wastewater, where removal percentages of 99.11% and 92% of cadmium and lead, respectively, were found. This modification shows as a result a considerable increase in the adsorption of lead and cadmium with respect to coal, which indicates that this adsorbent is favorable for the removal of heavy metals.